Peningkatan Kompetensi dan Kinerja Guru Dalam Kegiatan Belajar Mengajar Dengan Observasi Supervisi Kependidikan - Situmorang, Gepson (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This study aims to obtain an overview of the extent of mastery of the competence of SD Negeri Pangkalan teachers in carrying out teaching and learning activities. This school action research was carried out at the Pangkalan State Elementary School. The data obtained from the observations in the first cycle and second cycle the teacher's attitude in compiling and practicing in class was quite good, with an average value of 84.22. The teachers at SD Negeri Pangkalan are very enthusiastic in carrying out the preparation of lessons and practicing them well. From the results of the assessment of the implementation in the classroom, it is quite good. The conclusions that can be drawn from the results of this study are: (1) the competence of teachers in carrying out tasks, especially in the preparation of learning at SD Negeri Pangkalan can be improved properly, and (2) neglected factors in developing teacher competence in PBM, namely the utilization and use of manuals Lesson preparation does not get a good portion at SD Negeri Pangkalan.Keywords: supervising education; teacher competence; teacher performanceÃ‚Â Ã‚Â Abstrak: Penelitian ini bertujuan untuk memperoleh gambaran tentang sejauh mana penguasaan kompetensi guru SD Negeri PangkalanÃ‚Â dalam melaksanakan kegiatan belajar mengajar. Penelitian tindakan sekolah ini dilaksanakan diÃ‚Â SD Negeri Pangkalan. Data yang diperoleh dari hasil observasi pada siklus I dan siklus II sikap guru dalam menyusunÃ‚Â dan mempraktekkan di kelasÃ‚Â cukup baik, dengan rata-rata nilai 84,22.Ã‚Â Guru-guru di SD Negeri PangkalanÃ‚Â sangat antusian melaksanakan penyusunanÃ‚Â satuan pelajaran dan mempraktekkannya dengan baik. Dari hasil penilaian terhadap penilaian dalam implementatif di kelas cukup baik. Simpulan yang dapat diambil dari hasil penelitian ini adalah: (1) Kompetensi guru dalam melaksanakan tugas terutama dalam penyusunan satuan pelajaranÃ‚Â diÃ‚Â SD Negeri PangkalanÃ‚Â dapat ditanyakan baik, dan (2) Faktor yang terabaikan dalam pengembangan kompetensi guru dalam PBM yaitu pemanfaatanÃ‚Â dan penggunaan bukuÃ‚Â pedoman penyusunan satuan pelajaran kurang mendapatkan porsi yang baik diÃ‚Â SD Negeri Pangkalan.Kata Kunci: kinerja guru; kompetensi guru; supervise kependidikan